Basement geometry and sediment thickness of Lago Fagnano (Tierra del Fuego) - Esteban, Federico Damián (2014)
Lago Fagnano, an E-W elongated basin located in the central part of Isla Grande de Tierra del Fuego, occupies a structural depression originated along a segment of the Magallanes-Fagnano fault system. Its evolution was mostly conditioned by tectonic processes, and later was affected by glacial and glacio-lacustrine depositional events. New high-resolution single-channel seismic data, integrated with previous seismic profiles, and geological information acquired in the surroundings of the Lago Fagnano, allows us reconstructing the basement surface of the lake, and the geometry, distribution, and thickness of the glacial and glacio-lacustrine sequences. We recognized three main sub-basins within the Lago Fagnano: 1. a medium-size (ca. 21×5 km), deep (373 m), and asymmetric basin to the east; 2. an E-W trending (44×3 km), shallower (150 m) central sub-basin; and 3. a smaller (3.5×1.3 km), shallow (128 m) sub-basin to the west. The isopach sediment map shows that the most pronounced deposition occurred along the E-W axis of the lake, with a gradual increase in thickness towards east (from 100 to 150 m). The glacial deposits are widespread along the basin. The lacustrine sediments are preferentially localized along the E-W axis of the lake filling topographic lows. The shape of the sub-basins and their location in relation with the Magallanes-Fagnano fault system, along with the distribution, geometry, and thickness of the sedimentary units, show that the general morphology of the Lago Fagnano was mostly controlled by pre-existing and syntectonic features. Based on the structural data observed in the outcrops around the Lago Fagnano and the geophysical data, we proposed that the lake is composed by 4 amalgamated pull-apart sub-basins.